2003
DOI: 10.1038/sj.bmt.1703913
|View full text |Cite
|
Sign up to set email alerts
|

High-hyperdiploidy in Philadelphia positive adult acute lymphoblastic leukaemia: case-series and review of literature

Abstract: Summary:Patients with Philadelphia positive (Ph + ) adult acute lymphoblastic leukaemia (ALL) have a poor prognosis. Stem cell transplantation (SCT) is increasingly being recognised as the treatment of choice in eligible patients with Ph + ALL, but disease-relapse remains a problem in a proportion of patients prior to and after SCT. Genetic abnormalities in addition to the Ph chromosome may influence the biology and clinical course of ALL, but there are not many studies on the potential genetic heterogeneity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 12 publications
3
11
0
Order By: Relevance
“…The impact of additional chromosome abnormalities and BCR breakpoint on OS, EFS, RFS, and death in remission were examined by univariate analysis (Table 4). Both an extra Ph chromosome [ϩder (22)] and high hyperdiploidy (HeH) were associated with a significantly better RFS. It should be noted that 25 of 28 (89%) cases with HeH also had ϩder (22).…”
Section: Prognostic Factors For Outcomementioning
confidence: 99%
See 1 more Smart Citation
“…The impact of additional chromosome abnormalities and BCR breakpoint on OS, EFS, RFS, and death in remission were examined by univariate analysis (Table 4). Both an extra Ph chromosome [ϩder (22)] and high hyperdiploidy (HeH) were associated with a significantly better RFS. It should be noted that 25 of 28 (89%) cases with HeH also had ϩder (22).…”
Section: Prognostic Factors For Outcomementioning
confidence: 99%
“…Both an extra Ph chromosome [ϩder (22)] and high hyperdiploidy (HeH) were associated with a significantly better RFS. It should be noted that 25 of 28 (89%) cases with HeH also had ϩder (22). The RFS results were broadly consistent with the effects seen on OS and EFS, but these did not reach statistical significance.…”
Section: Prognostic Factors For Outcomementioning
confidence: 99%
“…High-hyper diploid ALL cases have shown that blasts have a marked propensity for apoptosis in vitro, which has been related to the relatively good in vivo response to chemotherapy. Reports from the literature also make it conceivable that the presence of high-hyper diploidy as an additional karyotypic abnormality may confer a better prognosis to Ph(+) ALL, presumably by altering the kinetics of Ph(+) neoplastic cells [11]. Chilton et al suggested, High-hyper diploidy is an important subtype of ALL at all ages and displays outcome heterogeneity according to chromosomal gain, however they did not find overall survival differences between Ph-positive HeH patients and Ph-negative patients (P=0.2: 50 vs 57% at 5 years) [12].…”
Section: Discussionmentioning
confidence: 99%
“…Metaphases were G-banded and the karyotype was described according to the ISCN 1995 [5]. 20 metaphases were analyzed which revealed the karyotype: 46,XY,t(9;22)(q34;q11) [4]/53,XY,+2,+4,+5,t(9;22)(q34;q11),+11,+14,+21,+der(22) t(9;22)(q34;q11) [14]/46,XY [2].…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation